Opieka zastępcza – od ekskluzji do inkluzji - Škoviera, Albín (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Writer raise an issue on inclusion and exclusion in three different levels. The firs level represents fulfiling child’s individual needs, the second level is about protection of other children’s interests and needs. Third level stends for actual social context with its own possibilities and limits. Writer points out the fact that ideology and its proclamations often don’t mach the applied proffesional solution. Experts face the pressure of political ambitions. Author gives several particular examples of “segregation” of – Romany (gypsy) ethnic minority, mentally disadvantaged children, disadvantaged children of intact popolation, international adoption. The writer is conviced that child in foster care is a part of whole children assembly and it is not appropriate to narrow the search for the optimal solution only for the child in foster care.